2021
DOI: 10.1016/j.acra.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Bulb MRI and Paranasal Sinus CT Findings in Persistent COVID-19 Anosmia

Abstract: Background and purpose There is limited literature consisting of case reports or series on olfactory bulb imaging in COVID-19 olfactory dysfunction. An imaging study with objective clinical correlation is needed in COVID-19 anosmia in order to better understand underlying pathogenesis. Material and methods We evaluated 23 patients with persistent COVID-19 olfactory dysfunction. Patients included in this study had a minimum 1-month duration between onset of olfactory dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
224
1
13

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(249 citation statements)
references
References 24 publications
11
224
1
13
Order By: Relevance
“…Available literature supports spontaneous improvement with a mean duration of 2-3 weeks [23,24]. However, cases with symptoms lasting more than 1 month, so called persistent anosmia, have also been reported [25][26][27]. Considering the fact that olfactory epithelium undergoes regeneration over 6-8 weeks, SARS-COV2 may result in anosmia longer than 2-3 weeks due to the epithelia damage caused [28].…”
Section: Clinical Features Of Covid-19 Anosmiamentioning
confidence: 99%
“…Available literature supports spontaneous improvement with a mean duration of 2-3 weeks [23,24]. However, cases with symptoms lasting more than 1 month, so called persistent anosmia, have also been reported [25][26][27]. Considering the fact that olfactory epithelium undergoes regeneration over 6-8 weeks, SARS-COV2 may result in anosmia longer than 2-3 weeks due to the epithelia damage caused [28].…”
Section: Clinical Features Of Covid-19 Anosmiamentioning
confidence: 99%
“…Future research should look for a way to quickly determine the COVID-19 severity using a global positioning system in target lung regions in 2-D and 3-D images, while considering comorbidity and time constraints [ 236 ] [ 237 ] [ 238 ]. This fundamental study can also be further developed in several other directions, covering the fields of neurology [ 239 ], cardiology, diabetology [ 240 ], and ophthalmology [ 241 ].…”
Section: Critical Discussionmentioning
confidence: 99%
“…Subsequently, hypotheses emerged regarding the potential for viral neurotropism and a direct route of entry into the CNS from the olfactory bulbs. In an imaging study 6 of 23 patients with confirmed SARS-CoV-2 infection with clinical anosmia, SARS-CoV-2-related olfactory dysfunction was differentiated from other viral olfactory dysfunction in several crucial ways. Post-viral anosmia in the setting of upper respiratory tract infections is usually related to mucosal congestion and nasal obstruction, resulting in a conductive olfactory loss; however, few patients with SARS-CoV-2-related anosmia had sinonasal symptoms, suggesting that mucosal congestion is an unlikely aetiology for anosmia in these cases.…”
mentioning
confidence: 99%
“…Post-viral anosmia in the setting of upper respiratory tract infections is usually related to mucosal congestion and nasal obstruction, resulting in a conductive olfactory loss; however, few patients with SARS-CoV-2-related anosmia had sinonasal symptoms, suggesting that mucosal congestion is an unlikely aetiology for anosmia in these cases. 6 Olfactory epithelium support-cells residing in the olfactory cleft express the angiotensin-converting enzyme 2 receptor, identified as the binding antigen for SARS-CoV-2. 6 Imaging of the olfactory cleft showed olfactory cleft opacification in 17 (74%) of cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation